Differential regulation of preovulatory luteinizing hormone and follicle-stimulating hormone release by opioids in the proestrous rat - Kumru, S; Simsek, M; Yilmaz, B; Sapmaz, E; Kutlu, S; Sandal, S; Canpolat, S (Acad Sciences Czech Republic, Inst Physiology, 2001)
We have investigated the role of mu- and kappa -opioid receptors in the central control of preovulatory LH and FSH release in the proestrous rat. Animals were anesthetized with chloral hydrate at 14:00 h on proestrus day. Following femoral artery cannulation, they were mounted in a stereotaxic apparatus. Morphine and U-50488H (benzene-acetamide methane sulphonate) were infused intracerebroventricularly either alone or in combination with naloxone and MR1452, respectively. Controls received sterile saline alone. Blood samples were obtained at hourly intervals between 15:00 h and 17:00 h. Plasma LH and FSH levels were measured by radio immunoassay. Morphine did not significantly change plasma LH levels at 15 00 h and 16:00 h sampling intervals. A significant increase was observed at 17:00 h compared to the controls (p<0.05). U-50488H significantly increased LH levels at 16:00 h and 17:00 It (p<0.05). The co-administration of naloxone and MR1452 with mu- and kappa -agonist had no significant effect on LH levels at any sampling interval. In all groups, LH levels showed a linear rise over the sampling period between 15:00 h and 17:00 h. None of the treatments significantly altered plasma FSH levels which however, declined towards the end of the afternoon surge. In conclusion, we suggest that the secretion of LH and FSH is differentially regulated by mu- and kappa -opioid receptors. It is thought that in all groups chloral hydrate interfered with the LH surge secretory systems.
Keywords: LH; FSH; morphine; naloxone; U-50488H; MR1452